Method for manufacturing separator for lithium secondary battery, separator for lithium secondary battery manufactured by the same, and lithium secondary battery having the same
By forming a porous coating containing bound polymer and inorganic particles on the porous polyphenol fat substrate of lithium-ion secondary batteries, and controlling the residual amount of bound polymer, the problem of reducing insulation after thinning of the separation membrane is solved, and a battery separation membrane with high energy density and long life is achieved.
Patent Information
- Application Number
- JP2023570427
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-05-19
- Filing Date
- 2023-03-02
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2043-03-02
AI Technical Summary
When the existing lithium-ion secondary battery separation membrane is thinned to 9 μm or below, the insulation is reduced, affecting the battery life.
A separation membrane with small average pore size and film characteristics was made by forming a porous coating containing binding polymer and inorganic particles on a porous polyphenol fat substrate and peeling multiple times by 3M tape to control the residual amount of binding polymer.
It is achieved to improve the insulation and life characteristics of the battery while maintaining high energy density, and avoid the occurrence of hole resistance.
Smart Images

Figure 0007669533000001
Abstract
Description
[Technical Field]
[0001] The present invention claims the benefit of the filing date of Korean Patent Application No. 10-2022-0061353, filed with the Korean Intellectual Property Office on May 19, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a separator for a lithium secondary battery, in which a porous coating layer containing a binder polymer and inorganic particles is formed on the surface of a porous polyolefin polymer substrate, a separator for a lithium secondary battery manufactured using the separator, and a lithium secondary battery including the separator. [Background technology]
[0003] As a separator for a lithium secondary battery, a porous substrate having a large number of pores and based on a polymer such as polyolefin is used.
[0004] To improve the heat resistance of such porous polymer substrates, a separator has been developed in which a porous coating layer containing a binder polymer and inorganic particles is formed on the surface of the polymer substrate.
[0005] The separator for lithium secondary batteries described above can have an average pore size of the porous polymer substrate adjusted depending on the application. For example, a separator for use in lithium secondary batteries for electric vehicles has an average pore size of about 40 to 80 nm in a porous polyolefin polymer substrate. The separator is manufactured by dispersing inorganic particles in a polymer solution in which a binder polymer is dissolved in a solvent to prepare a slurry, which is then coated on the surface of the porous polymer substrate and dried.
[0006] However, achieving high energy density requires thinner separators, but reducing the thickness of the porous polymer substrate to less than 9 μm poses the problem of reduced insulation of the separator. To solve this problem, adjusting the average pore size of the porous polymer substrate to, for example, less than 30 nm improves the insulation problem, but the binder polymer used to form the porous coating layer penetrates into the pores, further narrowing the pores that serve as the passageways for lithium ions, highlighting the problem of reduced battery life. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention provides a method for manufacturing a separator for a lithium secondary battery, which has an improved battery life characteristics while including a porous coating layer containing a binder polymer and inorganic particles and a thin porous polymer substrate.
[0008] Another object of the present invention is to provide a separator for a lithium secondary battery having the above-mentioned properties and a lithium secondary battery including the separator.
[0009] As will be readily apparent from the following description, the objects and advantages of the present invention can be realized by means of the instrumentalities or methods, and combinations thereof, as claimed. [Means for solving the problem]
[0010] The first aspect of the present invention includes the steps of: (S1) preparing a slurry in which binder polymer particles and inorganic particles are dispersed in an aqueous dispersion medium; and (S2) A method for preparing a separator for a lithium secondary battery, comprising the steps of coating the slurry on at least one surface of a porous polyolefin polymer substrate having a large number of pores and drying the coating to form a porous coating layer, The thickness of the porous polyolefin polymer substrate is 9 μm or less, The porous polyolefin polymer substrate has an average pore diameter of 30 nm or less, The porous coating layer was peeled off by applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.5 g / m 2 The following method for producing a separator for a lithium secondary battery is provided.
[0011] A second aspect of the present invention is the method for manufacturing the semiconductor device according to the first aspect, The porous polyolefin polymer substrate has an average pore diameter of 27 nm or less, The porous coating layer was peeled off by applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.45 g / m 2 The following method for producing a separator for a lithium secondary battery is provided.
[0012] A third aspect of the present invention is the method for manufacturing the semiconductor device according to the first aspect, The porous polyolefin polymer substrate has an average pore diameter of 25 nm or less, The porous coating layer was peeled off by applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.42 g / m 2 The following method for producing a separator for a lithium secondary battery is provided.
[0013] A fourth aspect of the present invention is any one of the first to third aspects, The slurry further includes a non-particulate binder polymer.
[0014] A fifth aspect of the present invention relates to the fourth aspect, The non-particulate binder polymer is present in an amount of 10 wt % or less based on the total weight of the binder polymer.
[0015] In a sixth aspect of the present invention, in any one of the first to fifth aspects, The binder polymer particles have an average particle size of 50 nm to 1000 nm.
[0016] A seventh aspect of the present invention is any one of the first to sixth aspects, The binder polymer particles are made of at least one polymer selected from the group consisting of polyvinyl fluoride-based polymers, acrylic polymers, vinyl-based polymers, and rubber-based polymers.
[0017] An eighth aspect of the present invention is A porous polyolefin polymer substrate having a large number of pores; and a porous coating layer formed on at least one surface of the porous polyolefin polymer substrate, the porous coating layer including a binder polymer and inorganic particles; The thickness of the porous polyolefin polymer substrate is 9 μm or less, The porous polyolefin polymer substrate has an average pore diameter of 30 nm or less, the binder polymer includes a particulate binder polymer; The porous coating layer was peeled off by applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.5 g / m 2 The following separator for a lithium secondary battery is provided:
[0018] A ninth aspect of the present invention is the method according to the eighth aspect, The porous polyolefin polymer substrate has an average pore diameter of 27 nm or less, The porous coating layer was peeled off by applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.45 g / m 2 The following separator for a lithium secondary battery is provided:
[0019] A tenth aspect of the present invention is the method for manufacturing the semiconductor device according to the eighth aspect, The porous polyolefin polymer substrate has an average pore diameter of 25 nm or less, The porous coating layer was peeled off by applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.42 g / m 2 The following separator for a lithium secondary battery is provided:
[0020] An eleventh aspect of the present invention is any one of the eighth to tenth aspects, The binder polymer may further include a non-particulate binder polymer, thereby providing a separator for a lithium secondary battery.
[0021] A twelfth aspect of the present invention is the method according to the eleventh aspect, The non-particulate binder polymer is an acrylic polymer having a Tg of 0° C. or less, and provides a separator for a lithium secondary battery.
[0022] A thirteenth aspect of the present invention is any one of the eighth to twelfth aspects, The non-particulate binder polymer is present in an amount of 10 wt % or less based on the total weight of the binder polymer, providing a separator for a lithium secondary battery.
[0023] A fourteenth aspect of the present invention is any one of the eighth to thirteenth aspects, The binder polymer particles have an average particle size of 50 nm to 1000 nm, providing a separator for a lithium secondary battery.
[0024] A fifteenth aspect of the present invention is any one of the eighth to fourteenth aspects, The binder polymer particles are made of at least one polymer selected from the group consisting of polyvinyl fluoride-based polymers, acrylic polymers, vinyl-based polymers, and rubber-based polymers, to provide a separator for a lithium secondary battery.
[0025] A sixteenth aspect of the present invention is any one of the eighth to fifteenth aspects, The binder polymer particles are an acrylic polymer having a Tg of 20° C. or higher, providing a separator for a lithium secondary battery.
[0026] A seventeenth aspect of the present invention provides a lithium secondary battery including an electrode assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein the separator is any one of the separators of the eighth to sixteenth aspects. [Effects of the Invention]
[0027] The present invention relates to a method for manufacturing a separator having a porous polymer substrate on the surface of which a porous coating layer containing a binder polymer and inorganic particles is formed. The method uses a thin porous polyolefin polymer substrate having a small average pore size, which enables realization of high energy density and good insulating properties. In addition, the method improves battery life characteristics by improving the pore blocking phenomenon that occurs with a small average pore size.
[0028] Therefore, the separator manufactured by this manufacturing method is very useful as a separator for a lithium secondary battery. DETAILED DESCRIPTION OF THE INVENTION
[0029] The present invention will be described in detail below. Prior to that, the terms and words used in the specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts that are consistent with the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of terms to best describe his or her invention. Therefore, it should be understood that the configurations described in the embodiments described in this specification are merely the most preferred embodiments of the present invention and do not represent the entire technical idea of the present invention, and that various equivalents and modifications that can replace them may exist at the time of filing this application.
[0030] Throughout this specification, when a part is said to "comprise" certain elements, this means that it may further include other elements, rather than excluding other elements, unless specifically stated to the contrary.
[0031] In the present specification, the property of having pores means that an object contains a plurality of pores, and the pores are interconnected to allow gas and / or liquid fluids to pass from one side of the object to the other side.
[0032] In the present specification, the separator has porous properties including a large number of pores and serves as a porous ion-conducting barrier that allows ions to pass through while blocking electrical contact between the negative electrode and the positive electrode in the electrochemical device.
[0033] Hereinafter, the method for producing a separator for a lithium secondary battery according to the present invention will be described in detail.
[0034] The method for manufacturing a separator for a lithium secondary battery according to the present invention includes: (S1) preparing a slurry in which binder polymer particles and inorganic particles are dispersed in an aqueous dispersion medium; and (S2) coating the slurry on at least one surface of a porous polyolefin polymer substrate having a plurality of pores, followed by drying to form a porous coating layer, The thickness of the porous polyolefin polymer substrate is 9 μm or less, The porous polyolefin polymer substrate has an average pore diameter of 30 nm or less, The porous coating layer was peeled off by applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.5 g / m 2 The following method for producing a separator for a lithium secondary battery is provided.
[0035] In the present invention, the porous polyolefin polymer substrate is manufactured using a polyolefin as a base polymer, as is well known. Examples of polyolefins include polyethylene, polypropylene, and polypentene, and one or more of these may be included. Such porous polymer substrates manufactured based on polyolefins, i.e., having a large number of pores, are advantageous from the viewpoint of imparting a shutdown function at an appropriate temperature. In particular, when polyethylene and polypropylene are simultaneously included as polyolefins, the shutdown property and physical properties such as mechanical strength can be simultaneously improved.
[0036] When preparing the polymer substrate, in addition to the polyolefin-based polymer described above, other polymer components may be further mixed as needed, and filler particles may also be included. The filler particles may be introduced for the purpose of acting as a pressure barrier to prevent excessive reduction in the thickness, pore size, and porosity of the separator substrate due to the high pressure applied during the lamination process. The filler particles may include organic or inorganic fillers having a predetermined particle size, and are not limited to a specific component as long as they have strength equal to or greater than that of the polyolefin resin.
[0037] In the present invention, the porous polyolefin polymer substrate has a thickness of 9 μm or less and an average pore diameter of 30 nm or less. Since such a porous polyolefin polymer substrate has a thickness of 9 μm or less, it is a thin film, which enables the realization of a lithium secondary battery having a high energy density. When the average pore diameter is 30 nm or less, the insulating properties of the thin film polymer substrate are ensured.
[0038] Specifically, the thickness of the porous polyolefin polymer substrate may be 8 μm or less, 7 μm or less, 6 μm or less, or 5 μm or less. However, the polyolefin polymer substrate may have a thickness of 4 μm or more to ensure the insulating properties of the separator. Preferably, the thickness of the polyolefin polymer substrate may be 4 μm or more and 8 μm or less. More preferably, the thickness may be 7 μm or more and 8 μm or less.
[0039] Specifically, the average pore size of the porous polyolefin polymer substrate may be 29 nm or less, 28 nm or less, 27 nm or less, 26 nm or less, 25 nm or less, 24 nm or less, 23 nm or less, 22 nm or less, or 21 nm or less. However, to ensure a path for lithium ion migration, the average pore size may be 20 nm or more. Preferably, the average pore size may be 20 nm or more and 25 nm or less.
[0040] The average pore diameter can be calculated from the pore size distribution measured using a capillary flow porometer. For example, the separation membrane to be measured is first wetted with a wetting agent such as Galwick solution, and then air pressure is gradually increased on one side of the substrate. When the applied air pressure exceeds the capillary attraction of the wetting agent present in the pores, the wetting agent blocking the pores is expelled. The size and distribution of the pores can be measured based on the pressure and flow rate at the moment of expulsion, and the average pore diameter (size) can be determined from this.
[0041] The porous polyolefin polymer substrate can be prepared as follows, but is not limited thereto.
[0042] In one embodiment of the present invention, the porous polyolefin polymer substrate can be manufactured by a dry process in which a polyolefin polymer is melt-extruded into a sheet and then stretched to induce microcracks between the lamellae, which are the crystalline portions of the polymer, to form micropores. Alternatively, the separator can be manufactured by a wet process in which a polyolefin polymer is mixed with a diluent at high temperature to form a single phase, followed by phase separation of the polymer material and the diluent during cooling, followed by extraction of the diluent to form pores. In this case, the pore size can be controlled by the stretching temperature and the MD / TD stretch ratio.
[0043] When a filler is added, the size of the filler particles may be 0.001 μm to less than 100 μm. Preferably, the filler particles may have a particle size of 0.01 μm to 0.1 μm, and may be appropriately adjusted within this range in consideration of the target thickness of the separation membrane substrate after the lamination process.
[0044] According to the production method of the present invention, the slurry in which binder polymer particles and inorganic particles are dispersed in an aqueous dispersion medium can be prepared as follows (step S1).
[0045] The inorganic particles constituting the skeleton of the porous coating layer are not particularly limited as long as they are electrochemically stable. For example, inorganic particles that can be used in the present invention can be used in the range of the operating voltage of the applied battery (e.g., Li / Li + There are no particular limitations on the material as long as it does not undergo oxidation and / or reduction reactions at a voltage (0 V to 5 V relative to the reference voltage).
[0046] Examples of the inorganic particles include high-dielectric-constant inorganic particles having a dielectric constant of 1 or more, preferably 10 or more, inorganic particles having piezoelectricity, and inorganic particles having lithium ion transport ability.
[0047] That is, examples of inorganic particles include SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, AlOOH, Al(OH)3, TiO2, and SiC, and one or more of these may be used in combination, but are not limited to these.
[0048] Piezoelectric inorganic particles are non-conductors under normal pressure, but when a certain amount of pressure is applied, their internal structure changes, allowing them to conduct electricity. These piezoelectric inorganic particles have a high dielectric constant of 100 or more. When tensioned or compressed by a certain amount of pressure, they generate an electric charge. One side is positively charged and the other side is negatively charged, creating a potential difference between the two sides. When using these piezoelectric inorganic particles, if an internal short circuit occurs between the two electrodes due to an external impact such as a local crush or a nail, the piezoelectricity of the inorganic particles creates a potential difference within the particles, which allows electrons to move between the two electrodes, i.e., a minute current to flow, resulting in a gradual decrease in the battery voltage and improved safety. Examples of inorganic particles with piezoelectricity include BaTiO3, Pb(Zr,Ti)O3 (PZT), and Pb 1-x La x Zr 1-y Ti y O3(PLZT), Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnia (HfO2) or mixtures thereof, but are not limited thereto.
[0049] Inorganic particles having lithium-ion conduction ability refer to inorganic particles that contain lithium elements and have the function of moving lithium ions without storing lithium. Inorganic particles having lithium-ion conduction ability can transmit and move lithium ions due to a kind of defect existing inside the particle structure, so the lithium-ion conductivity in the battery can be improved, and thereby the battery performance can be enhanced. Examples of inorganic particles having lithium-ion conduction ability include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y -based glasses such as 14Li2O - 9Al2O3 - 38TiO2 - 39P2O5 (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate such as Li 3.25 Ge 0.25 P 0.75 S4 (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride such as Li3N (Li x Ge y P z S w , 0 < x < 4, 0 < y < 2), SiS2 - based glasses such as Li3PO4 - Li2S - SiS2 (Li x Si y S z Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5 - based glasses such as LiI - Li2S - P2S5 (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), or mixtures thereof, etc., but not limited thereto.
[0050] The particle size of the inorganic particles is not limited, but is preferably in the range of 0.001 μm to 10 μm to form a porous coating layer of uniform thickness and with an appropriate porosity. The pore size of the porous coating layer can be controlled by adjusting the particle size of the inorganic particles used, the amount of binder polymer particles mixed, and the content of non-particulate binder polymer dissolved in the aqueous dispersion medium optionally included.
[0051] The binder polymer particles dispersed in the slurry connect and fix inorganic particles, thereby providing adhesion to the porous coating layer and the polyolefin polymer substrate and electrode. Because the binder polymer particles are insoluble in the aqueous dispersion medium, they maintain the particle shape they have when added to the slurry, typically, but not limited to, circular particles. In the present invention, "particles" refers to particles that do not dissolve in the dispersion medium in the slurry and maintain their particle shape at temperatures of 20°C or less. They preferably maintain their particle shape at temperatures of 30°C or less, and more preferably, at temperatures of 35°C or less.
[0052] Such binder polymer particles maintain their particulate shape even after assembly into a battery and hardly penetrate the pores of the porous polyolefin polymer substrate, thereby contributing to improving the pore blocking phenomenon that occurs due to the small average pore size of the polyolefin polymer substrate. From this perspective, binder polymer particles having an average particle size of 50 nm to 1000 nm can be used, but are not limited thereto.
[0053] Any binder polymer particles can be used without limitation as long as they can impart adhesive strength to the electrode. For example, polymer particles made of one or more polymers selected from the group consisting of polyvinyl fluoride-based polymers, acrylic-based polymers, vinyl-based polymers, and rubber-based polymers can be used.
[0054] Examples of polyvinyl fluoride-based polymers include polyvinylidene fluoride or copolymers thereof; examples of rubber-based polymer particles include styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber, and acrylonitrile-butadiene-styrene rubber; and examples of acrylic polymer particles include copolymers of butyl acrylate and ethylhexyl acrylate, and copolymers of methyl methacrylate and ethylhexyl acrylate.
[0055] Other examples include, but are not limited to, polyacrylonitrile, polyvinylchloride, polycyanoacrylate, and vinylidene fluoride-hexafluoropropylene copolymer.
[0056] In particular, an acrylic polymer having a Tg of 20° C. or higher can be used as the binder polymer particles, more specifically, an acrylic polymer having a Tg of 30° C. or higher, and even more specifically, an acrylic polymer having a Tg of 35° C. or higher can be used. In particular, an acrylic polymer having a Tg of 20° C. to 100° C. can be used, more specifically, an acrylic polymer having a Tg of 30° C. to 60° C., and even more specifically, an acrylic polymer having a Tg of 35° C. to 50° C. can be used.
[0057] The aqueous dispersion medium is a hydrophilic liquid such as water or alcohol that does not dissolve the inorganic particles and binder polymer particles. The slurry is produced by adding the binder polymer particles and inorganic particles to the aqueous dispersion medium, mixing them, and dispersing them.
[0058] A dispersant may be further added to the slurry as needed.
[0059] In addition to the binder polymer particles, i.e., particulate binder polymers, the slurry may further contain non-particulate binder polymers. As used herein, "non-particulate" refers to a polymer that is soluble in the aqueous dispersion medium of the aqueous slurry or that is insoluble in the aqueous dispersion medium but loses its particulate form depending on the temperature, e.g., transforms into a film-like form at temperatures above 18°C. The particulate form is preferably lost at temperatures above 15°C, more preferably above 10°C.
[0060] Examples of non-particulate binder polymers that dissolve in aqueous dispersion media include, but are not limited to, polyvinyl alcohol and carboxymethyl cellulose. Examples of non-particulate binder polymers that do not dissolve in aqueous dispersion media but lose their particulate form at a predetermined temperature include, but are not limited to, acrylic polymers with a Tg of 0°C or less. Non-particulate binder polymers that do not dissolve in aqueous dispersion media but lose their particulate form at a predetermined temperature retain their non-particulate form in the finally formed porous coating layer.
[0061] The content of the non-particulate binder polymer may be 10 wt% or less based on the total weight of the polymer binder. Specifically, the content of the non-particulate binder polymer may be 9 wt% or less, 8 wt% or less, 7 wt% or less, 6 wt% or less, or 5 wt% or less based on the total weight of the binder polymer contained in the slurry. If the content of the non-particulate binder polymer exceeds 10 wt%, pore clogging may occur.
[0062] The mixing ratio (weight ratio) of the inorganic particles to the binder polymer particles in the slurry can be, for example, 50:50 to 99:1, more specifically, 60:40 to 99:1, but is not limited to this.
[0063] The prepared slurry is coated on at least one surface of a porous polyolefin polymer substrate and dried to form a porous coating layer (step S2). A conventional coating method can be used to coat the polymer substrate with the slurry. Dip coating, die coating, roll coating, comma coating, or a combination of these methods is preferred. The drying method is performed by appropriately setting the temperature and time conditions to minimize the occurrence of surface defects in the porous coating layer. A drying auxiliary device such as a drying oven or hot air can be used within an appropriate range.
[0064] In the manufacturing method of the present invention, the porous coating layer is peeled off by a method of attaching and then removing 3M Scotch tape three times, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate is 0.5 g / m 2 Form it so that it looks like this:
[0065] After peeling under the above peeling conditions, the amount of the binder polymer component remaining on the porous polyolefin polymer substrate is 0.5 g / m 2 If the average pore diameter exceeds 27 nm, the battery life characteristics will be reduced due to the pore blocking phenomenon caused by the small average pore diameter. In this regard, specifically, the average pore diameter of the porous polyolefin polymer substrate is 27 nm or less, and the porous coating layer is peeled off by a method of applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate is 0.45 g / m or less. 2 More specifically, the porous polyolefin polymer substrate has an average pore size of 25 nm or less, and the porous coating layer is peeled off by a method of applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate is 0.42 g / m or less. 2 It can be the following:
[0066] The separator for a lithium secondary battery manufactured by the above method is A porous polyolefin polymer substrate having a large number of pores; and a porous coating layer formed on at least one surface of the porous polyolefin polymer substrate, the porous coating layer including a binder polymer and inorganic particles; The thickness of the porous polyolefin polymer substrate is 9 μm or less, The porous polyolefin polymer substrate has an average pore diameter of 30 nm or less, the binder polymer includes a particulate binder polymer; The porous coating layer was peeled off by applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.5 g / m 2 The following is the result.
[0067] Specifically, the porous polyolefin polymer substrate has an average pore size of 27 nm or less, and the porous coating layer is peeled off by applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate is 0.45 g / m. 2 More specifically, the porous polyolefin polymer substrate has an average pore size of 25 nm or less, and the porous coating layer is peeled off by a method of applying 3M Scotch tape three times and then removing it, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate is 0.42 g / m or less. 2 It can be the following:
[0068] As described above, the non-particulate binder polymer may be present in an amount of 10 wt % or less based on the total weight of the binder polymer. The binder polymer particles may have an average particle size of 50 nm to 1000 nm. The binder polymer particles may be made of one or more polymers selected from the group consisting of polyvinyl fluoride-based polymers, acrylic polymers, vinyl-based polymers, and rubber-based polymers. The binder polymer particles may be an acrylic polymer having a Tg of 20°C or higher.
[0069] In one embodiment of the present invention, the porosity of the porous coating layer may be 30 vol% to 70 vol% of the porosity of the heat-resistant layer, and the thickness of the porous coating layer may be, but is not limited to, 0.5 μm to 3 μm based on the cross-sectional coating.
[0070] The separator for a lithium secondary battery described above is interposed between a positive electrode, a negative electrode, and the positive and negative electrodes to form an electrode assembly, which is then manufactured into a lithium secondary battery. That is, the separator for a lithium secondary battery prepared by the above method is interposed between a negative electrode and a positive electrode, and the electrode assembly is manufactured by a lamination process in which heat and / or pressure are applied to bond them. In one embodiment of the present invention, the lamination process can be performed using a roll press device including a pair of pressure rollers. That is, the negative electrode, separator, and positive electrode can be sequentially stacked and then inserted between the pressure rollers to achieve interlayer bonding. In this case, the lamination process can be performed using a hot press method.
[0071] The positive electrode comprises a positive electrode current collector and a positive electrode active material layer on at least one surface of the current collector, the positive electrode active material layer including a positive electrode active material, a conductive material, and a binder resin. The positive electrode active material can be a layered compound such as lithium manganese composite oxide (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2), or lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; 1+x Mn 2-xO4 (where x is from 0 to 0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, Cu2V2O7; chemical formula LiNi 1-x M x O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga and x = 0.01 to 0.3), Ni-site type lithium nickel oxides represented by; chemical formula LiMn 1-x M x O2 (where M = Co, Ni, Fe, Cr, Zn or Ta and x = 0.01 to 0.1) or lithium manganese composite oxides represented by Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of the Li in the chemical formula is substituted with alkaline earth metal ions; disulfide compounds; It can contain one or a mixture of two or more of Fe2(MoO4)3.
[0072] The negative electrode includes a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material, a conductive material, and a binder resin on at least one surface of the current collector. As the negative electrode active material, the negative electrode includes carbon such as lithium metal oxide, graphitized carbon, and graphite-based carbon; Li x Fe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8), etc. metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; It can contain one or a mixture of two or more selected from titanium oxides.
[0073] The conductive material may be, for example, any one selected from the group consisting of graphite, carbon black, carbon or metal fiber, metal powder, conductive whiskers, conductive metal oxide, activated carbon, and polyphenylene derivatives, or a mixture of two or more of these conductive materials. More specifically, the conductive material may be any one selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide, or a mixture of two or more of these conductive materials.
[0074] The current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery. For example, stainless steel, copper, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like can be used.
[0075] As the binder resin, a polymer that is commonly used for electrodes in the industry can be used. Non-limiting examples of such binder resins include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polyethylhexyl acrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. Examples of suitable cellulose acetate copolymers include, but are not limited to, cyanoethyl acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxyl methyl cellulose.
[0076] The electrode assembly prepared as described above can be placed in a suitable case and an electrolyte injected to manufacture a battery.
[0077] The electrolyte is A + B- A salt having the structure: + Li + , Na + , K. + or a combination thereof, - is PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 - or a salt containing an anion such as, or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or a mixture thereof.
[0078] A battery module including a battery having the electrode assembly as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source can be provided. Specific examples of the device include, but are not limited to, power tools powered by a battery-powered motor, electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters, electric golf carts, and power storage systems.
[0079] The present invention will be described in detail below with reference to examples. However, the examples of the present invention can be modified in various different forms, and the scope of the present invention should not be construed as being limited to the examples detailed below. The examples of the present invention are provided to more completely explain the present invention to those skilled in the art.
[0080] [Example 1] As the porous polyolefin polymer substrate, a wet polyethylene separator membrane with a thickness of 8 μm and a porosity of 45% manufactured by Toray Industries was used.
[0081] The polyethylene separator has a porosity of 45%, an average pore size of 25 μm, and a puncture strength of 250 gf.
[0082] Meanwhile, the slurry was prepared as follows.
[0083] Al2O3 (Sumitomo, D 50An inorganic particle dispersion was prepared by adding 20g of (500nm), 0.89g of polyacrylic acid dispersant solution (42% solids), and 20g of 0.5mm beads to 30.5g of a 95:5 water:ethanol mixture and stirring for 2 hours on a paint shaker. Next, 10.9g of a particulate binder polymer (particle size 350nm, Tg 40°C) made from a copolymer of methyl methacrylate and ethylhexyl acrylate dispersed in water at 41wt% as the binder component (particle size 350nm, Tg 40°C) and 0.17g of a surfactant (3M FC4430, 90% solids) were added to the inorganic particle dispersion and shaken to prepare a coating slurry (ratio of inorganic to binder polymer particles + additives in the slurry solids = 80:20).
[0084] The coating slurry was filtered through a 200 mesh filter, coated onto one side of a polyethylene porous film using a bar coater, and then dried in a dryer. The other side of the film was coated again under the same conditions to produce a double-coated separator. The coating thickness was controlled to 5 μm based on the total thickness of the double-sided coating.
[0085] [Example 2] The inorganic particle dispersion was prepared in the same manner as in Example 1, except that 10 g of a particulate binder polymer (particle size 350 nm, Tg 40°C) of a copolymer of methyl methacrylate and ethylhexyl acrylate dispersed in water at 41 wt % and 0.94 g of an acrylic resin (Toyochem CSB130, particle size 150 nm, Tg -30°C) dispersed in water at 40 wt % were added as binder components to the inorganic particle dispersion.
[0086] [Comparative Example 1] Al2O3 (Sumitomo, D 5020g of PVDF-HFP (molecular weight 400,000, HFP 8w%) and 15.5g of PVDF-HFP (molecular weight 500,000, HFP 15w%) dissolved in acetone at a concentration of 10wt% were added to the inorganic particle dispersion and stirred for 2 hours on a paint shaker to prepare a coating slurry (ratio of inorganic to binder components + additives in the slurry solids = 80:20).
[0087] The coating slurry was filtered through a 200 mesh and then dip-coated on both sides of a polyethylene porous film at 23°C and 45% RH, followed by drying in a dryer. The coating thickness was controlled to 5 μm based on the total thickness of the double-sided coating.
[0088] Comparative Example 2 The wet polyethylene separation membrane was produced in the same manner as in Comparative Example 1, except that a separation membrane having an average pore size of 40 nm and a thickness of 8 μm was used.
[0089] Comparative Example 3 The wet polyethylene separation membrane was produced in the same manner as in Comparative Example 1, except that a separation membrane having an average pore diameter of 40 nm and a thickness of 9 μm was used.
[0090] Comparative Example 4 The wet polyethylene separation membrane was produced in the same manner as in Example 1, except that a separation membrane having an average pore diameter of 40 nm and a thickness of 8 μm was used.
[0091] Comparative Example 5 The wet polyethylene separator was prepared in the same manner as in Example 1, except that an 8 μm thick separator with an average pore size of 40 nm was used, and 9.09 g of a particulate binder polymer (particle size 350 nm, Tg 40°C) of a copolymer of methyl methacrylate and ethylhexyl acrylate dispersed in water at 41 wt % and 1.88 g of an acrylic resin (Toyochem CSB130, particle size 150 nm, Tg -30°C) dispersed in water at 40 wt % were added to the inorganic particle dispersion as binder components.
[0092] [Measuring the average pore diameter] The measurement was based on the pore size distribution using a capillary flow porometer (CFP method).
[0093] [Measurement of the amount of binder polymer component remaining on the porous polyolefin polymer substrate after peeling off the porous coating layer by adhering the porous coating layer with 3M Scotch tape three times and then removing it]
[0094] The porous coated separators of the Examples and Comparative Examples were cut into 8 cm x 8 cm pieces, and 5 mm of each edge was secured to a glass plate with tape to prevent wrinkles. Then, multiple pieces were attached together using 3M tape (810D) to cover the entire surface of the porous coating layer. After holding for 5 seconds, the tape was removed. After two more rounds of coating layer removal using 3M tape (a total of three rounds), the separators with the cross-sectional coating layer removed were cut into 7 cm x 7 cm pieces. Next, the separators were inverted onto a glass plate so that the coating layer on the opposite side was exposed, and 5 mm of each edge was secured with tape. 3M tape (810D) was again used for three rounds of coating layer removal. Finally, the separators with the coating layers removed from both sides were cut into 5 cm x 5 cm pieces and weighed. The same fabric as used for coating was cut into a 5cm x 5cm piece, weighed, and compared to the weight to calculate the binder impregnation per square meter.
[0095] [Measurement of breakdown voltage after compression] A 10cm x 10cm piece of release PET was laminated on the top and bottom of a 5cm x 5cm piece of separation membrane. The release side of the release PET was in contact with the separation membrane. The PET-laminated separation membrane was hot pressed for 10 seconds at a temperature of 70°C and a pressure of 5.2 MPa to produce a compressed separation membrane sample.
[0096] The prepared coating separator sample was placed between aluminum jigs (upper jig diameter 30 mm, lower jig 50 mm x 100 mm), and the voltage at which the fail condition (>0.5 mA, 3 seconds) occurred was measured using a Hi-pot tester. The measurement conditions were DC, current 0.5 mA, and voltage increase 100 V / s (up to 3 kV).
[0097] [Measurement of capacity retention rate after 200 cycles at 25℃, 1C / 1C]
[0098] Cathode manufacturing Cathode active material (LiNi 0.8 Mn 0.1 Co 0.1 O2), conductive material (carbon black), dispersant, and binder resin (a mixture of PVDF-HFP and PVDF) were mixed with water in a weight ratio of 97.5:0.7:0.14:1.66 to prepare a slurry for the positive electrode active material layer with a concentration of 50 wt% of the remaining components excluding water. The slurry was then applied to the surface of an aluminum thin film (10 μm thick) and dried to prepare a positive electrode having a positive electrode active material layer (120 μm thick). Anode manufacturing Graphite (a blend of natural and artificial graphite), conductive material (carbon black), dispersant, and binder resin (a mixture of PVDF-HFP and PVDF) were mixed with water in a weight ratio of 97.5:0.7:0.14:1.66 to prepare a slurry for the negative electrode active material layer, with the remaining components (excluding water) at a concentration of 50 wt%. The slurry was then applied to the surface of a copper thin film (10 μm thick) and dried to prepare a negative electrode having a negative electrode active material layer (120 μm thick).
[0099] Lamination process The prepared negative electrode and positive electrode were stacked with the separators of the Examples and Comparative Examples interposed therebetween, and a lamination process was performed to obtain an electrode assembly using a hot press at 70°C and 5.2 MPa for 10 seconds.
[0100] Electrolyte injection A monocell was fabricated using the electrode assembly fabricated according to the lamination process, and an electrolyte solution of ethylene carbonate / ethyl methyl carbonate = 3:7 (volume ratio) in which 1M LiPF6 was dissolved was injected into the monocell to fabricate a lithium secondary battery.
[0101] The battery manufactured by the above method was repeatedly charged and discharged at 25°C and at a rate of 1C in the range of 2.5V to 4.25V, and the ratio of discharge capacities after 200 cycles was calculated.
[0102] [Table 1]
Claims
1. (S1) preparing a slurry in which binder polymer particles and inorganic particles are dispersed in an aqueous dispersion medium; and (S2) A method for preparing a separator for a lithium secondary battery, comprising the steps of coating the slurry on at least one surface of a porous polyolefin polymer substrate having a large number of pores and drying the slurry to form a porous coating layer, The thickness of the porous polyolefin polymer substrate is 9 μm or less; The porous polyolefin polymer substrate has an average pore size of 30 nm or less; The porous coating layer was peeled off by applying and then removing 3M Scotch (registered trademark) tape (810D) three times, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.5 g / m 2 The following is a method for producing a separator for a lithium secondary battery.
2. The porous polyolefin polymer substrate has an average pore size of 27 nm or less; The porous coating layer was peeled off by applying and removing 3M Scotch tape (810D) three times, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.45 g / m 2 The method for producing a separator for a lithium secondary battery according to claim 1, wherein the separator is:
3. The porous polyolefin polymer substrate has an average pore size of 25 nm or less; The porous coating layer was peeled off by applying and removing 3M Scotch (registered trademark) tape (810D) three times, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.42 g / m 2 The method for producing a separator for a lithium secondary battery according to claim 1, wherein the separator is:
4. The method of claim 1 , wherein the slurry further comprises a non-particulate binder polymer.
5. The method of claim 4, wherein the non-particulate binder polymer is present in an amount of 10 wt% or less based on the total weight of the binder polymer.
6. 2. The method of claim 1, wherein the binder polymer particles are made of at least one polymer selected from the group consisting of polyvinyl fluoride-based polymers, acrylic polymers, vinyl-based polymers, and rubber-based polymers.
7. A porous polyolefin polymer substrate having a large number of pores, and a porous coating layer formed on at least one surface of the porous polyolefin polymer substrate, the porous coating layer including a binder polymer and inorganic particles; The thickness of the porous polyolefin polymer substrate is 9 μm or less; The porous polyolefin polymer substrate has an average pore size of 30 nm or less; The binder polymer includes a particulate binder polymer, The porous coating layer was peeled off by applying and then removing 3M Scotch (registered trademark) tape (810D) three times, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.5 g / m 2 The separator for a lithium secondary battery is as follows:
8. The porous polyolefin polymer substrate has an average pore size of 27 nm or less; The porous coating layer was peeled off by applying and removing 3M Scotch tape (810D) three times, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.45 g / m 2 Below is the The separator for a lithium secondary battery according to claim 7.
9. The porous polyolefin polymer substrate has an average pore size of 25 nm or less; The porous coating layer was peeled off by applying and removing 3M Scotch (registered trademark) tape (810D) three times, and the amount of the binder polymer component remaining on the porous polyolefin polymer substrate was 0.42 g / m 2 Below is the The separator for a lithium secondary battery according to claim 7.
10. The separator for a lithium secondary battery according to claim 7 , wherein the binder polymer further comprises a non-particulate binder polymer.
11. The separator for a lithium secondary battery according to claim 10, wherein the non-particulate binder polymer is an acrylic polymer having a Tg of 0° C. or less.
12. The separator for a lithium secondary battery according to claim 10, wherein the non-particulate binder polymer is present in an amount of 10 wt % or less based on the total weight of the binder polymer.
13. 8. The separator for a lithium secondary battery according to claim 7, wherein the particulate binder polymer is at least one polymer selected from the group consisting of polyvinyl fluoride-based polymers, acrylic polymers, vinyl-based polymers, and rubber-based polymers.
14. The separator for a lithium secondary battery according to claim 7, wherein the particulate binder polymer is an acrylic polymer having a Tg of 20° C. or more.
15. A lithium secondary battery having an electrode assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, The separator according to any one of claims 7 to 14, wherein the separator is a lithium secondary battery.
Citation Information
Patent Citations
Electrochemical device and electronic device
CN113363671A
Separator for secondary battery including an organic-inorganic composite porous layer and method for manufacturing the same
JP2017538248A
Composite separator for secondary battery and lithium secondary battery including the same
JP2019102453A
Separator and electrochemical element including same
JP2019505974A
Porous polyolefin film
JP2020069796A